2014
DOI: 10.1016/j.atherosclerosis.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D modulates the association of circulating insulin-like growth factor-1 with carotid artery intima-media thickness

Abstract: Objective Experimental evidence indicates that circulating insulin-like growth factor-1 (IGF-1) counteracts vascular aging and atherosclerosis, for which increased carotid artery intima-media thickness (IMT) is a marker. Yet, IGF-1 concentrations have been inconsistently associated with carotid IMT in epidemiological studies. Since vitamin D is also implicated in vascular protection and affects IGF-1 biology, we hypothesized that it would influence the effect of IGF-1 on IMT. Methods The relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…6 Reduced expression of IGF-1 contributes to apoptosis of pulmonary fibroblasts 6 and endothelial cells. 48 Although we found that Cr supplementation increased the IGF-1 expression in bronchial epithelial cells and in pulmonary vascular cells, IGF-1 did not seen to play an important role in our I/R model. Furthermore, our results indicate that Cr may inhibit apoptosis of bronchial epithelial and endothelial cells, a phenomenon that involved in the formation of pulmonary edema.…”
Section: Figurementioning
confidence: 60%
“…6 Reduced expression of IGF-1 contributes to apoptosis of pulmonary fibroblasts 6 and endothelial cells. 48 Although we found that Cr supplementation increased the IGF-1 expression in bronchial epithelial cells and in pulmonary vascular cells, IGF-1 did not seen to play an important role in our I/R model. Furthermore, our results indicate that Cr may inhibit apoptosis of bronchial epithelial and endothelial cells, a phenomenon that involved in the formation of pulmonary edema.…”
Section: Figurementioning
confidence: 60%
“…Serum 25(OH)D3 may be partially protected by inhibition of inflammation (e.g., inhibition of abnormal angiogenesis and vascular endothelial dysfunction [22]). Besides, a previous study conducted in Italy revealed that circulation of IGF-1 is a major vascular protection factor at low circulation levels of vitamin D, and the mechanism is that IGF-1 strengthens the antioxidant and anti-apoptotic effects in endothelial cell culture [23]. Therefore, it can be concluded that the role of IGF-1 in disease is different.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kawachi et al [77] showed that IGF-1 levels were correlated with CC-IMT in non-obese individuals, and Splicke et al [78] showed a positive correlation between serum IGF-1/IGFBP-3 ratio and CC-IMT [77,78]. Ameri et al [79] found an interesting negative association of IGF-1 with CC-IMT only in patients in the lowest 25-hydroxyvitamin D quartile in the Baltimore Longitudinal Study of Aging (BLSA) and the Microalbuminuria: A Genoa Investigation on Complications (MAGIC) study [79]. Abd El-Hafiz et al [80], in a comparative study of metabolically healthy obese individuals with healthy controls, also suggested that IGF-1 is protective against CC-IMT in the presence of low serum vitamin D [80].…”
Section: <Stroke>mentioning
confidence: 94%